Modelling a Process of UAV Data Collection and Processing - Čermáková, Ivana; Komárková, Jitka (Infonomic Society, 2016)
Utilization of Unmanned Aerial Vehicle (UAV) for observing landscape is rapidly increasing because it is fast a fast way which provides data on demand with an appropriate resolution. Data are suitable for next processing and analyses and the whole procedure is reasonably cheap. It is necessary to propose and describe a suitable process for data collection and processing to repeatedly obtain correct results. Thus, the paper proposes the whole procedure of UAV data collection, preprocessing, classification and indices calculation. The selected aspects of the process are described in a graphical form of various process diagrams (process map, data flow diagram and indicators matrix). The paper describes a case study which is focused on an identification of a small water body (pond Pohranov near Pardubice city in the Czech Republic) shoreline to demonstrate the whole process. The provided graphical description allows standardise the whole process, choose suitable data and an appropriate way of their analysis (e.g. indicators matrix). Main advantage of the proposed procedure is applicability on various data sources and areas of interest.
Modelování procesu výběru a zpracování dat z UAV
Keywords: UAV; Data collection; Data processing; Classification; Index calculation; UAV; Zpracování dat; Klasifikace; Indexy